Clinical pathways for pancreatic surgery: are they a suitable instrument for process standardization to improve process and outcome quality of patients undergoing distal and total pancreatectomy? : a retrospective cohort study - Téoule, Patrick; Römling, Laura Anja; Schwarzbach, Matthias; Birgin, Emrullah; Rückert, Felix; Wilhelm, Torsten J.; Niedergethmann, Marco; Post, Stefan; Rahbari, Nuh Nabi; Reißfelder, Christoph; Ronellenfitsch, Ulrich (Therapeutics and clinical risk management, 2019)
Purpose: Pancreatic surgery demands complex multidisciplinary management, which is often cumbersome to implement. Clinical pathways (CPs) are a tool to facilitate this task, but evidence for their utility in pancreatic surgery is scarce. This study evaluated if CPs are a suitable tool for process standardization in order to improve process and outcome quality in patients undergoing distal and total pancreatectomy. Patients and methods: Data of consecutive patients who underwent distal or total pancreatectomy before (n=67) or after (n=61) CP introduction were evaluated regarding catheter management, postoperative mobilization, pancreatic enzyme substitution, resumption of diet and length of stay. Outcome quality was assessed using glycaemia management, morbidity, mortality, reoperation and readmission rates. Results: The usage of incentive spirometers for pneumonia prophylaxis increased. The median number of days with hyperglycemia decreased significantly from 2.5 to 0. For distal pancreatectomy, the incidence of postoperative diabetes dropped from 27.9% to 7.1% (p=0.012). The incidence of postoperative exocrine pancreatic insufficiency decreased from 37.2% to 11.9% (p=0.007). There was no significant difference in mortality, morbidity, reoperation and readmission rates between groups. Conclusion: Following implementation of a pancreatic surgery CP, several indicators of process and outcome quality improved, while others such as mortality and reoperation rates remained unchanged. CPs are a promising tool to improve quality of care in pancreatic surgery.